An Assessment of Spontaneous Vegetation Recovery in Aggregate Quarries in Coastal Sand Dunes in Buenos Aires Province, Argentina - Fernandez Montoni, Maria Victoria (2014)
Sand dune quarries are a location of common aggregate mining activity developed in coastal areas, especially in the southeast Buenos Aires province, Argentina. In this article, spontaneous plant development after extraction activity ceased was evaluated. Five areas (three quarried and two natural/conservation areas) were sampled for plant cover and composition as well as sediment characterization. Different indexes, principal component analysis, and cluster analyses were applied to compare the areas. The dominant families observed in four of the five areas were Asteraceae, Poaceae, and Cyperaceae, and most of the species are commonly found in sandy and humid soils and/or modified/anthropized ones. Percentages of plant cover increased with time because of the cessation of active aggregate extraction. Indexes and multivariate analyses showed that it was possible to distinguish quarried and natural areas based on composition and vegetation cover. The distribution of plant species among the four areas responded to the presence of mining activity, but it also responded to the topographical position and consequently the depth of the groundwater level. Besides these differences, the four areas shared many native species. The results might indicate that once the activity has ceased, quarried areas may spontaneously and quickly develop a plant community with some similarities to those present in the nonquarried areas. However, given that the extracting activity involves the removal of the soil, revegetation of this type of environment depends on the presence of natural areas in the surroundings, which can serve as a source of seeds and propagules for plant regeneration.